2005
DOI: 10.1074/jbc.m500338200
|View full text |Cite
|
Sign up to set email alerts
|

Mg2+ and Ca2+ Differentially Regulate DNA Binding and Dimerization of DREAM

Abstract: DREAM (calsenilin/KChIP3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
158
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(177 citation statements)
references
References 42 publications
16
158
3
Order By: Relevance
“…Even an EF3,EF4 fragment (amino acid 161 – 256) of KChIP3 showed a reduced spectral resolution in the absence of Ca 2+ , corroborating the central role of EF3 and EF4 in Ca 2+ binding and associated conformational changes [40]. KChIPs may also form oligomers in a divalent cation-dependent manner, with Ca 2+ binding to EF3 and EF4 favoring dimer formation [33,39,41]. KChIP3 has even been reported to oligomerize with calcineurin and calmodulin [42].…”
Section: Ca2+ Binding Properties and Associated Conformational Changementioning
confidence: 87%
See 4 more Smart Citations
“…Even an EF3,EF4 fragment (amino acid 161 – 256) of KChIP3 showed a reduced spectral resolution in the absence of Ca 2+ , corroborating the central role of EF3 and EF4 in Ca 2+ binding and associated conformational changes [40]. KChIPs may also form oligomers in a divalent cation-dependent manner, with Ca 2+ binding to EF3 and EF4 favoring dimer formation [33,39,41]. KChIP3 has even been reported to oligomerize with calcineurin and calmodulin [42].…”
Section: Ca2+ Binding Properties and Associated Conformational Changementioning
confidence: 87%
“…The experimental results showed that KChIPs are able to bind both Ca 2+ and Mg 2+ via their EF-hands, and that they exhibit high and low affinity Ca 2+ binding (Figure 2) [1,3439]. K d values for high affinity Ca 2+ binding range between 10 and 50 μM, and for low affinity Ca 2+ binding between 2 and 3 mM [35,37,38].…”
Section: Ca2+ Binding Properties and Associated Conformational Changementioning
confidence: 99%
See 3 more Smart Citations